Morphometry, productivity and bromatological analisis of purple elephant grass according to nitrogen fertilization - João Paulo Farias Ramos; José Thyago Aires Souza; Rubens Fernandes Costa; Raimundo Ribeiro Ferreira; Iara Tamires Rodrigues Cavalcante; Ricardo Miranda Leite; Selma Soares Santos; Valdemir Ribeiro Cavalcante (Acta Scientiarum. Animal Sciences, 2021)
The objective was to evaluate the morphometric, productive and chemical aspects of purple elephant grass as a function of nitrogen fertilization. The treatments consisted of applying 0, 20, 40, 60, and 80 kg ha-1 of N, using a randomized block design, with five treatments and four replications. The following were evaluated: plant height, number, length and leaf mass, stem diameter and mass, leaf/stem ratio, production of green and dry mass, support capacity for dairy cows, crude protein, neutral detergent fiber and mineral matter. The data were submitted to analysis of variance and Tukey's test at 5% probability. The increase in N doses did not affect (p < 0.05) the morphometry of the purple elephant grass, however it positively stimulated the productivity, the animal support capacity and the bromatological components of the harvested material. The lack of response to nitrogen fertilization may be related to the edaphocilimatic conditions during the experiment and efficiency in the use of N of the variety used. The results demonstrate the high demand of the cultivar for N, actively interfering in the forage yield.